Lower‐limb amputation following foot ulcers in patients with diabetes: classification systems, external validation and comparative analysis. Issue 5 (6th April 2015) - Monteiro‐Soares, Matilde; Martins‐Mendes, Daniela; Vaz‐Carneiro, António; Dinis‐Ribeiro, Mário
Abstract Background This study aimed to validate and compare the existing systems developed to stratify subjects with diabetic foot ulcers by risk of consequent lower extremity amputation. Methods We conducted a prospective cohort study on a consecutive series of patients (mean age of 68 years; 64% male) with active ulcer who were attending our Hospital Diabetic Foot Clinic (n = 293) from January 2010 to March 2013. At baseline, we collected information on the participants' characteristics and the relevant variables. Afterwards, we assessed the predictive value of each variable and each system's prognostic accuracy for amputation occurrence. Results During a median follow‐up of 91 days (interquartile range of 98), ulcers healed in 62% of the subjects. Major amputation occurred in 7% and minor occurred in 17%. Previous ulcer or amputation, ulcer area, and gangrene were associated with amputation occurrence. Nephropathy, pulses number, ulcer aetiology, depth, and number were associated with risk of amputation. Systems typically presented sensitivity values ≥80% and negative likelihood ratios ≤0.5 for the highest risk group; area under the receiver operating characteristic curve ranged from 0.56 to 0.83 and positive likelihood ratios from 1.0 to 5.9. If one chose only major amputation as an outcome, positive predictive values were lower, and negative predictive values tended to be higher. Conclusions System stages, grades, scores, and/or prognostics were generally associated with amputation, presenting overall substantial accuracy values. Nevertheless, great improvement is possible. A multicentre study validating and refining the existing systems is needed to improve clinical decision‐making in this area. Copyright © 2014 John Wiley & Sons, Ltd.